Anatomical feasibility study of unilateral percutaneous kyphoplasty for lumbar through the conventional transpedicular approach: An observational study using 3D CT analysis. Issue 37 (September 2018) - Wang, Hongwei; Hu, Pan; Wu, Deluo; Zhang, Ning; Wu, Jun; Chen, Yu; Xiang, Liangbi
Abstract : Abstract: The aim of the study was to discuss the significance of sex, level, age, and side in relation to the anatomical distinctions of unilateral percutaneous kyphoplasty (PKP) for lumbar osteoporotic vertebral compression fractures (OVCFs) through the conventional transpedicle approach (CTPA). We have retrospectively collected lumbar spines (L1–L5) of 200 patients and simulated PKP on the 3D CT scans through unilateral CTPA. We have measured the distance between the entry point and the midline of the vertebral body (DEM), the puncture inclination angle (PIA), safe range of the inner inclination angles (SRA), and the success rate (SR) of puncture. Significant differences ( P  < .05) between the male and female for L1 to L5, left and right side for L1 to L3 in the mean DEM were shown. The DEM from L1 to L5 was significantly increased ( P  < .05) from (20.6 ± 2.0) mm to (29.8 ± 2.9) mm. For L1 to L5, the right maximum PIA was significantly larger than the left. The maximum PIA and SRA in the male was significantly larger than that in the female. The SRA from L1 to L5 was significantly increased ( P  < .05) from (19.5 ± 5.9)° to (48.9 ± 8.1)°. The SR in male was significantly higher than that in female for L1 to L4. There were no significant differences in the SR between different age groups except for L4. The SR from L1 to L5 was significantly increased ( P  < .05) from 26.3% to 99.0%. DEM was 20.6 to 29.8 mm according to different levels. The value of DEM, PIA, SRA, and SR was significantly increased from L1 to L5. No significant differences in the SR between right and left for L1 to L5, different age groups except for L4 were observed.